(untitled) (Zdravstveni glasnik, 2024)
Introduction: The formation of a stable identity plays an important role throughout life, but it becomes a key developmental task during the period of adolescence and emerging adulthood. Objective: Examine the role of different dimensions of perfectionism and personal growth initiative in the explanation of identity styles in emerging adulthood. Method: A total of 228 participants (28 male and 200 female) between the ages of 18 and 28 from Bosnia and Herzegovina, Croatia, Serbia and Montenegro took part in the research. The data was collected by filling out an online questionnaire that used the Identity Style Inventory, the Positive and Negative Perfectionism Scale and the Personal Growth Initiative Scale. Results: Young men scored higher on Positive perfectionism and Intentional behavior than young women. A significant positive association of the Diffuse-avoidant identity style with Negative perfectionism was obtained, as well as its negative association with all personal growth initiative components. Informational and Normative style were positively related to both components of perfectionism, with the fact that Informational style was also positively related to all personal growth initiative components. Lower Positive and higher Negative perfectionism proved to be significant predictors of the Diffuse style, while higher Positive and Negative perfectionism predicted Informational and Normative style. Conclusion: Different components of perfectionism and personal growth initiative significantly contribute to the process of identity formation in emerging adulthood.